DECISION INFORMATION SYSTEM AND ANNOUNCEMENT OF FINE AND COSTS FOR WEB-BASED TRAFFIC BREACHES AT THE LUBUKLINGGAU STATE COURT - Armanto Armanto; Taufik Rahman (Jurnal TAM (Technology Acceptance Model), 2020)
The Lubuklinggau District Court Office is a judicial institution whose duties are to receive, examine and decide cases of traffic violations. Mechanisms for resolving cases of traffic violations in Lubuklinggau, starting from delegation, decisions, making reports and access to information are still done manually because there is no direct integrated system between the Police, the Court and the Community. From the problems at hand, the authors are interested in creating a Web-based Information System for Decisions and Announcement of Fines and Ticketing Case Fees which is expected to facilitate the process of resolving ticket cases. The method used for this research is the method of data collection, by making direct observations to the research site (observation), conducting direct questions and answers to sources (interviews), documentation and literature study by reading literature books. This system is built using the PHP programming language, MySQL database, and Sublite Text as a program listing, the waterfall system development method, system testing is carried out using black box testing. This system can be a solution to the problems faced by the Court and the Police in processing ticket data that is well-systemed and integrated and the public can easily access e-ticket information in the system and the system created will improve services at the Lubuklinggau city district court. This results in the output of accessing the online decision announcement by the public affected by the ticketing case.